Traceable Size and Size Distribution Calibrations of Nanoparticles. Issue 3 (20th December 2016) - Buhr, Egbert; Dziomba, Thorsten; Frase, Carl Georg; Krumrey, Michael; Bosse, Harald
Abstract: Quality control of nanoparticle production processes requires traceable calibration methods for size and size distribution which are presented and discussed in this article. The main focus is on the one hand the application of small‐angle X‐ray scattering for an integral measurement of nanoparticles in liquid suspension and on the other hand scanning electron microscopy in transmission for a microscopic measurement method of nanoparticles prepared on a substrate. In addition, characterization by scanning probe microscopy is covered. Abstract : At the German National Metrology Institute methods for traceable calibration of nanoparticle size were developed. Small‐angle X‐ray scattering measures nanoparticles in suspension, while scanning electron microscopy in transmission and scanning probe microscopy are applied for nanoparticles prepared on a substrate.